The primary hydrogen kinetic isotope effect in the elimination from 2-phenethyl systems : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science with Honours in Chemistry at Massey University - Woodhead, John Leslie (Massey University, 1974)
The primary kinetic isotope effects for the base-catalysed E2 elimination from a series of substituted 2-phenethyl bromides and 2-phenethyldimethylsulphonium bromides in dimethyl sulphoxide-water as solvent at 20° have been measured. A broad maximum in the isotope effect was observed for the 2-phenethyl bromides. The Hammett p value for each reaction series at 20° has also been determined and both were large and positive. Arrhenius plots using the kH/kD ratios for each of the p-MeO substituted compounds at 20°, 30° and 40° were carried out to determine the importance of proton tunnelling in these reactions. The usefulness of the primary Kinetic isotope effect as a measure of proton position in the E2 transition states for these reactions is discussed.
Some Dutch language throughout
Keywords: Chemical kinetics; Protons